Monetary policy coordination: A new empirical approach - Paul R. Bergin; Oscar Jordá (University of California, Department of Economics, 2000)
This paper examines the degree of monetary policy coordination between major industrialized countries from a completely new perspective. The analysis uses a new data set on central bank issued interest rate targets for 14 OECD countries. The methodology that we use decomposes the notion of coordination into two components: (1) Do countries coordinate the timing of their monetary policy actions? and (2) Is there coordination in the direction in which targets are changed? The answers to these two questions are based on a newly developed dynamic discrete duration model (the autoregressive conditional hazard model or ACH) and on an ordered response model in event time. The results indicate there is significant policy coordination among these 14 countries during the 1980-1998 sample period in contrast to recent theoretical work suggesting that gains to coordination are small. Moreover, this coordination appears to work through channels other than documented coordination agreements.
Keywords: F42; E58; F47; 330; monetary policy; international coordination; interest rate targets; Geldpolitik; Internationale wirtschaftspolitische Koordination; Geldpolitisches Ziel; Zins; Schätzung; OECD-Staaten